A299 RARE CASE OF CONGENITAL DEFECT IN THE COLONIC MUSCULARIS PROPRIA EXTERNA CAUSING COLONIC PSEUDO OBSTRUCTION AND SEVERE CONSTIPATION IN A 10-YEAR-OLD BOY. (1st March 2018) - Greenaway, E D; Langer, J; Scaini, V; Ngan, B; Marcon, P
Abstract: Background: In children chronic constipation is common, usually functional and appropriate treatment regimens can be developed. When unresponsive to traditional therapy other etiologies are explored. Colonic intestinal pseudo obstruction (IPO) is a rare cause of severe chronic constipation. Aims: A 2-year-old toilet trained male developed a Streptococcal perianal infection, painful defecation with stool withholding behaviours and chronic constipation unresponsive to medical management. He thrived with no anorexia or vomiting. He had a history of complex febrile seizures which resolved by age 6 years. He developed significant anxiety around stooling and received counselling. Family history revealed functional constipation in 4 maternal cousins. Physical examinations revealed a well grown, developmentally appropriate boy, with a normal physical exam other than copious stool on abdominal palpation. Rectal examination was unremarkable. Methods: Contrast barium enema was normal. Anorectal manometry showed low squeeze pressure and ineffective bear-down but present RAIR. Full thickness rectal biopsy revealed normal ganglion cells. Immunostain for calretinin showed normal expression within mucosal nerve fibres. Nuclear medicine gut transit study demonstrated a normal pattern of gastric emptying and small bowel transit time with no evidence of colonic inertia or regional bowel abnormality. MRI of the spine, upper and lower endoscopies, celiac disease screen and abdominal ultrasound were normal. Radiography showed faecal loading primarily in the rectosigmoid region. He had treatment trials of PEG3350, Pico Salax®, Senna, prucalopride and anal sphincter botulinum toxin injection without improvement. Results: He had placement of a cecostomy tube for antegrade colonic enemas and rectosigmoid resection with colorectal anastomosis. The resected segment was 5cm in circumference at the narrow margin and 15cm at the dilated margin. For 12cm extending to the narrow margin, the tenia coli separated into 2 separate longitudinal bands exposing the underlying inner circular muscular layer which appeared as cross-connecting ridges. Sections taken from the narrower segment with split tinea coli showed extensive thinning of the muscularis propria externa. Immunostains for interstitial cells of Cajal showed either absence or sparse numbers. He had one admission shortly after surgery for faecal impaction but has since managed to keep the colon clear with a cecostomy irrigation regimen. Conclusions: There are few cases described of segmental congenital defects of the intestinal musculature resulting in IPO. The few cases described note hypertrophy, supernumerary muscular layers or hypoplasia, primarily involving the small bowel. This case adds to the small body of literature describing such abnormalities in the colon. Funding Agencies: None